Erianin, a promising agent in the treatment of glioblastoma multiforme triggers apoptosis in U373 and A172 glioblastoma cells - Serter Koçoğlu, Sema; Seçme, Mücahit; Elmas, Levent (Archives of Biological Sciences, 2022)
Paper description: Erianin is a dibenzyl compound derived from Dendrobium chrysotoxum In human U373 and A172 glioblastoma cancer cells erianin induces apoptosis by inhibition of B-cell lymphoma 2 (Bcl-2), caspase-8, caspase-9 and tumor necrosis factor receptor type 1-associated DEATH domain protein (TRADD), and activation of caspase-3 and BH3 interacting domain death agonist (BID) gene expression. Erianin reduces invasion and migration in glioblastoma cells. Erianin may be a promising agent in the treatment of glioblastoma. Abstract: Glioblastoma is an aggressive, common and deadly primary intracranial brain tumor in adults. The antitumor activity of erianin, a dibenzyl compound found in Dendrobium chrysotoxum Lindl. extract, has not been previously demonstrated in glioblastoma. We investigated the anticancer activity and underlying mechanisms of erianin in human U373 and A172 glioma cells. The effects of erianin on cell viability, apoptosis, migration and invasion were estimated by the XTT test, the reverse transcription-polymerase chain reaction (RT-PCR)/annexin V wound healing assay, and Matrigel® invasion chamber, respectively. The effective amounts of erianin in U373 and A172 cells were 16 and 64 μM at 48 h, respectively. Erianin also significantly induced apoptosis by inhibiting B-cell lymphoma 2 (Bcl-2), caspase-8, caspase-9 and tumor necrosis factor receptor type 1-associated DEATH domain protein (TRADD), and activation of caspase-3 and BH3 interacting domain death agonist (BID) gene expression. In addition, erianin significantly increased the number of apoptotic cells in U373 and A172 cells and significantly decreased invasion and migration in U373 and A172 cells. Taken together, our results suggest that erianin may be a new therapeutic anticancer drug component with a potent apoptotic effect and a potential for treating glioblastoma.